Large scale ab initio modeling of structurally uncharacterized antimicrobial peptides reveals known and novel folds - Kozic, Mara (2020)
Antimicrobial resistance within a wide range of infectious agents is a severe and growing public health threat. Antimicrobial peptides (AMPs) are among the leading alternatives to current antibiotics, exhibiting broad spectrum activity. Their activity is determined by numerous properties such as cationic charge, amphipathicity, size, and amino acid composition. Currently, only around 10% of known AMP sequences have experimentally solved structures. To improve our understanding of the AMP structural universe we have carried out large scale ab initio 3D modeling of structurally uncharacterized AMPs that revealed similarities between predicted folds of the modeled sequences and structures of characterized AMPs. Two of the peptides whose models matched known folds are Lebocin Peptide 1A (LP1A) and Odorranain M, predicted to form β-hairpins but, interestingly, to lack the intramolecular disulfide bonds, cation-π or aromatic interactions that generally stabilize such AMP structures. Other examples include Ponericin Q42, Latarcin 4a, Kassinatuerin 1, Ceratotoxin D, and CPF-B1 peptide, which have α-helical folds, as well as mixed αβ folds of human Histatin 2 peptide and Garvicin A which are, to the best of our knowledge, the first linear αββ fold AMPs lacking intramolecular disulfide bonds. In addition to fold matches to experimentally derived structures, unique folds were also obtained, namely for Microcin M and Ipomicin. These results help in understanding the range of protein scaffolds that naturally bear antimicrobial activity and may facilitate protein design efforts towards better AMPs.